Protective effect of L-carnitine in cyclophosphamide-induced germ cell apoptosis - Zhu, Bin (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
Cyclophosphamide (CP) is a widely used anti-cancer agent; however, it can also induce serious male infertility. There are currently no effective drugs to alleviate this side-effect. L-Carnitine has been used to treat male infertility, but whether it can be used to protect against CP-induced male infertility is still unclear. This study aims to explore the effect and mechanism of L-carnitine in male infertility induced by CP. CP was used to establish an animal model. After three weeks of treatment, rats were sacrificed and testis and serum were harvested for further evaluation. Testosterone and estrogen levels were measured by enzyme-linked immunosorbent assay (ELISA). Testicular injury was examined by hematoxylin and eosin (H & E) staining, and germ-cell apoptosis was evaluated by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL). The expression of LC3 and Beclin-1 was examined by immunohistochemistry, Western blot, and real-time polymerase chain reaction (PCR), respectively. Compared with the CP group, L-carnitine significantly increases sperm motility, viability, and testosterone level (P<0.05). Western blot and real-time PCR results showed that L-carnitine treatment can significantly up-regulate the LC3-II and Beclin-1 expression in the CP+L-carnitine group when compared with the control group (P<0.05). In addition, TUNEL-positive cells were also more numerous in the CP group; however, L-carnitine can effectively retard cell apoptosis in the CP+L-carnitine group. In conclusion, L-carnitine contributes to the inhibition of cell apoptosis and the modulation of autophagy in protecting CP-induced testicular injury. These results suggest the applicability of L-carnitine in the treatment of male infertility.